The Teacher’s Role in The Implementation of Curriculum Merdeka in English Classroom - Zaitun Qamariah; Siti Anisah (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2023)
The Independent curriculum is a new curriculum used in Indonesia and a transitional curriculum from K-13 curriculum. Therefore, this study aims to examine how the role of a teacher in implementing the new curriculum in the class they teach, especially English teachers. This study used library research methods, the data were taken from several articles and similar research. The source of data came from Google Scholar by using keywords the role of the teacher in the independent curriculum and the application of the independent curriculum in English classes. The results of this study indicate that English teachers are people who play an important role in implementing the independent curriculum. The English teacher in this curriculum acts as a giver of understanding, and has influence to improve the quality of education as well as an adapter that aligns the curriculum with the characteristics and needs of students. English teachers can implement an independent curriculum by changing teaching methods, using new strategies to improve learning outcomes. For curriculum implementation there are several strategies that English teachers can use such as games, music, using interactive learning media when teaching, then you can also use Role-play, Information-gap activities, Jigsaw activities, open-ended discussions and debates.